Understanding food insecurity and overweight or obesity in Canada - Li, Tim; Fafard St-Germain, Andrée-Anne (My University, 2024)
Limited research exists on the relationship between household food insecurity, the inadequate or insecure access to food due to financial constraints, and overweight or obesity in Canada. This study helps address this knowledge gap by using population representative data of measured height and weight, rather than self-reported. It also uses propensity score weighting, a statistical technique that better accounts for the systemic differences in the characteristics of those who live in food-secure and food-insecure households. Public health interventions often conflate food insecurity and obesity, so understanding the relationship between these two public health problems is necessary for identifying and implementing appropriate responses.
Keywords: Children & youth; Health; Income, pensions, spending & wealth